Parents’ perceptions of the impact of the novel coronavirus (COVID-19) on the eating behaviors and routines of children with autism spectrum disorders (ASD) - Alharbi, Mudi H. (Frontiers in Psychiatry, 2024)
Restricted interests and repetitive behavior are characteristics of autism spectrum disorder (ASD).The likelihood that persons with ASD will respond adversely to unfamiliar situations is great. The novel coronavirus outbreak has resulted in disruptions to all aspects of routine and behavior.Hence, this study proposed to investigate the impact of the outbreak on the eating behavior and routines of children with ASD in Saudi Arabia through the perceptions of their parents.A cross-sectional study with a quantitative approach was utilized to obtain data from 150 parents of children with ASD aged ≤18 years in Saudi Arabia. The data collected included demographic data of the parents, the ASD status of the family, impact of COVID-19 to the family, eating behavior of the children with ASD, and daily routines of the children with ASD. Moreover, parents were able to provide comments regarding their children's eating behavior or daily routines.The study found that changes in the eating behavior of children with ASD were found to differ significantly (p<0.05) based on the number of children with ASD, the age of the children with ASD, the gender of the children with ASD, and the severity of their ASD symptoms. Moreover, changes to dinner-time routines were found to differ significantly (p<0.05) based on the age of the children with ASD. Also, changes to morning routines were found to differ significantly (p<0.05) based on the age of the children with ASD, their gender, and the severity of their ASD symptoms.Additionally, impact of COVID-19 to the family had a significant impact to eating behavior and daily routines of the children with ASD.This study found that the eating behavior and daily routines of children with ASD in Saudi Arabia have been considerably worsened and changed. The study recommends the collaboration of multidisciplinary teams and parents to modify or design interventions that help to change their eating behavior and routine can be implemented in the home. It also recommends the provision of virtual helplines to aid parents of children with ASD in such cases.